(3GdEYdGe GdEJUGd h GdMhGQ (B:s (3af h Yde (B/s - (3TQja, eUWais ((3GdLRGFQ (B:s (3OGQ gheg ddWHGYI h GdfTQ ,s, 2018)
(3GdSdWI GdQGHYI GUHMJ gj GdSdWI GdGhdi h GdeLJeYGJ Gd(B\(3jf jJMcehf aj Yde h af GdGYdGe h GdJUGd h GdMhGQ jhGLghf GdJMOjGJ HbhI GdeDda gfG jTQM dfG efgL g(B\(3G GdYde NGUI GdGYdGe HUaI YGeI jQcR Ydi GdeUGFH h GdchGQK h GdTQ GdQgGf jecf aj JZjjQ g(B\(3G GdefWb dfMbb GdJYGjT GdSdej h GdJaGge h GdJbQH Hjf GdTYhH g(B\(3G GdcJGH ehVhY GdSGYIs
Keywords: (3GdGJUGds; (3GdMhGQs; (3Ydes; (3GdEYdGes